2017
DOI: 10.1111/ggi.13131
|View full text |Cite
|
Sign up to set email alerts
|

Association of care recipients’ care‐need level with family caregiver participation in health check‐ups in Japan

Abstract: Aim:The public mandatory long-term care insurance system in Japan has supposedly mitigated the care burden for family caregivers of older adults, whereas family caregivers still play a considerable role in providing care. The effect of informal caregiving on the caregiver's health has been of great interest. We investigated the relationship between the amplitude of informal caregiving and caregiver participation in health check-ups in Japan.Methods: The present study was a cross-sectional analysis of nationall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 18 publications
0
16
0
1
Order By: Relevance
“… Milte et al (2019) 19 Ageing & Society Argentina Qualitative methodologies 2016–2017 The paper conducted a clandestine audit by older people living in the community and found that there has been a rapid growth in the availability of formal services, but that there are many gaps in provision, especially for older people with complex care needs. Purpose 2: Effects of LTCI on the financial burden on the caretakers and their families Sugiyama et al (2018) 20 Geriatrics & Gerontology International Japan Cross-sectional analysis 2010 The present study was a cross-sectional analysis of nationally representative data in Japan (2010 Comprehensive Survey of Living Conditions). It is found that, facilitating health check-up participation for family caregivers of care recipients with higher care-need levels might be an effective intervention for decreasing the gap in health behavior possibly caused by informal caregiving.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… Milte et al (2019) 19 Ageing & Society Argentina Qualitative methodologies 2016–2017 The paper conducted a clandestine audit by older people living in the community and found that there has been a rapid growth in the availability of formal services, but that there are many gaps in provision, especially for older people with complex care needs. Purpose 2: Effects of LTCI on the financial burden on the caretakers and their families Sugiyama et al (2018) 20 Geriatrics & Gerontology International Japan Cross-sectional analysis 2010 The present study was a cross-sectional analysis of nationally representative data in Japan (2010 Comprehensive Survey of Living Conditions). It is found that, facilitating health check-up participation for family caregivers of care recipients with higher care-need levels might be an effective intervention for decreasing the gap in health behavior possibly caused by informal caregiving.…”
Section: Resultsmentioning
confidence: 99%
“…Sugiyama et al believed that Japan’s public compulsory LTCI system alleviated the nursing burden of home caregivers for the elderly. 20 Iwamoto and Saito found that LTCI (Long-Term Care Insurance) helps Japanese families to reduce the welfare losses associated with disabled family members. 21 Other Japanese scholars Tamiya have different views, and he thinks the LTCI was challenged by the dissatisfaction of necessary support for the family caregivers and the sustainability of the system.…”
Section: Resultsmentioning
confidence: 99%
“…With the information, we defined the family caregivers who take care of the care recipients as the primary study participants. This algorithm to define the family caregiver is used in previous studies using the CSLC [ 26 , 27 ]. We included participants aged 40 years or older because there were very few younger caregivers with cancer [ 28 ] and it is also the target age for cancer screening in Japan [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…The care-need level was classified as "support required" (2 levels) or "care required" (5 levels) according to Japan's long-term care insurance system [34]. Based on a previous study, we apportioned the care-need level into three categories: lower need level (support required levels 1 and 2), middle need level (care required levels 1-3) and higher need level (care required levels 4 and 5) [14]. We defined gender, educational attainment, household equivalized income, and care-need level as categorical variables.…”
Section: Other Variablesmentioning
confidence: 99%
“…Focusing on family caregivers, a study suggests that while female family caregivers are at higher risk of hypertension compared with non-caregivers, the caregivers have had fewer annual health checkups and therefore need some support to receive these [13]. It was also reported that a higher care-need level in care recipients was negatively associated with family caregivers' participation in health checkups [14].…”
Section: Introductionmentioning
confidence: 99%